Hubungan Penggunaan AI Generatif dengan Kemampuan Berpikir Kreatif Generasi Z di Kabupaten Pemalang - Wahyu Jati Lelono; Diryo Suparto; Didi Permadi (Universitas Medan Area, 2026)
This study examines the relationship between the use of generative Artificial Intelligence (AI) and Generation Z's creative thinking skills in digital activities in Pemalang Regency, Indonesia. Although research on generative AI has expanded rapidly, most previous studies have focused on formal educational settings, leaving its role in Generation Z's everyday digital activities relatively underexplored. This study employed a quantitative correlational design involving 100 Generation Z respondents selected through purposive sampling. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed using descriptive statistics, normality and linearity tests, and Spearman's rank correlation with IBM SPSS Statistics 25. The findings indicate that generative AI usage is at a high level (mean = 73.65), while creative thinking skills are categorized as good (mean = 64.01). The correlation analysis reveals a positive and statistically significant relationship between generative AI usage and creative thinking skills (ρ = 0.475; p < 0.05). These findings suggest that generative AI can function as a creative enabler, supporting idea generation and creative development in digital activities when used critically, responsibly, and proportionally. This study contributes empirical evidence to the growing literature on generative AI and creativity by examining Generation Z's everyday digital practices within a local Indonesian context.